The Reflection of Religious Heritage in the Poetry of Samih-ul-Qasim, the Palestinian Resistance Poet - Mohammad Khaqani Isfahani; Maryam Jalaei (دراسات في اللغة العربيّة وآدابها)
Being inspired by the human heritage is of the most prominent features of the modern Arabic poetry, which has outstandingly featured in the Palestinian resistance poems. So, it is not an exaggeration if we maintain that this poetry has been deeply affected by the religious heritage of its context, as religion holds a significant place in the consciousness of the Arabs particularly the Palestinians. Therefore, the poems of Samih-ul-Qasim as one of the pioneers of Palestinian resistance literature must be supported and informed by religious ideas either directly or indirectly, like the other literary figures of this land. The present research examines, descriptively and analytically, the religious heritage as reflected in the poetical works of this poet. Also, it evaluates his ability and the extent of the correspondence his work with the religious heritage. It is concluded that the poet has a great ability and skill in connecting the past and the present and taking benefit from human heritage to enrich his work of literature.